MANAJEMEN KEARSIPAN PADA DINAS PEMBERDAYAAN MASYARAKAT DAN DESA KABUPATEN BANGGAI KEPULAUAN - Sampelan, Verny A.; Waris, Irwan; Nawawi, Muh. (Katalogis, 2018)
The purpose of this study is to describe the management of records in the General Subdivision of the PMD Service in Banggai Kepulauan Regency. This type of research is descriptive, with the number of informants involved as many as 5 informants, which for determining the informants using Purposive Sampling techniques. In addition, in the technique of data collection in this study through observation, interviews, and documentation activities With the method of data analysis with steps namely (1) data reduction, (2) data display, and (3) conclusion and verification. From the results of the research, it is known that the implementation of archival management of the General Subdivision of the PMD Service of Banggai Islands Regency is still running less optimally, because the three aspects (planning, implementation and supervision) which are used as indicators in this study are considered to run less optimally, this is because: 1) In terms of planning, planning activities are only limited to the design of budgeting and procurement of archival equipment, even though the archival management system and the development of archival HR management also need to be planned in order to ensure clarity in the implementation of archival management in the agency properly and correctly; 2) In terms of implementation, so far in the process of storing the archives there are still a number of letters that have not been archived, even though when viewed from the date of entry, some of these letters should have been filed. Other problems are also in the arrangement of archives, there are still problems, where documents are still mixed with different types and functions, making it difficult to find the required records; and 3) In terms of supervision, maintenance of records in the General Sub-Section of the PMD Service of Banggai Kepulauan Regency is still rarely done, besides that there has also been no concrete effort to do file depreciation through the destruction of records that have no value so that the files are abandoned and piled up inside the storage warehouseÂ